Comprehensive Molecular Serology of Human Chlamydia trachomatis Infections by Peptide Enzyme-Linked Immunosorbent Assays - K. Shamsur Rahman (American Society for Microbiology, 2018)
ABSTRACT Sensitive species-specific detection of anti-Chlamydia trachomatis antibodies is compromised by cross-reactivity of the C. trachomatis antigens used in standard microimmunofluorescence (MIF) testing and enzyme-linked immunosorbent assays (ELISAs). Previously, we discovered 48 strongly reactive C. trachomatis-specific B cell epitope peptides from 21 immunodominant proteins. Here we comprehensively evaluated the 11 top-ranked C. trachomatis-specific peptide antigens from 8 proteins for use in C. trachomatis serology. Sera from 125 women with nucleic acid amplification test (NAAT)-confirmed active C. trachomatis infection and from 49 healthy women with a low risk of C. trachomatis infection were used as anti-C. trachomatis antibody-positive and -negative sera. Results obtained for detection of IgG1, IgG3, and IgA1 antibodies against the 11 C. trachomatis peptide antigens were compared to results from 4 commercial anti-C. trachomatis IgG ELISAs. Using composite reference standards (CRS) of all assays for anti-C. trachomatis antibody status, commercial ELISAs detected antibodies in antibody-positive women with sensitivities of 51.5% to 64.8%. In contrast, a combination of the results of all 11 peptides detected IgG (IgG1 and IgG3) antibodies with 91.8% sensitivity, and a labor-saving combination of the 5 optimal peptides still detected antibodies in antibody-positive women with 86.5% sensitivity (all at 98% specificity). The superior performance of the combined peptide ELISAs was confirmed by area under the receiver operating characteristic curve (ROC-AUC), likelihood ratio, and predictive value analyses. The higher sensitivity of the peptide assays results from using multiple B cell epitopes of several C. trachomatis immunodominant proteins, including OmpA, compared to exclusively using the OmpA antigens used in commercial ELISAs. Thus, ELISAs with combined use of synthetic peptide antigens for C. trachomatis antibody detection have the advantage of simultaneous high sensitivity and high specificity. IMPORTANCE For detection of anti-Chlamydia trachomatis antibodies by serological assays, use of classical whole-organism chlamydial antigens results in high cross-reactivity. These antigens bind mainly antibodies against the major outer membrane protein (OmpA) and bind antibodies against other immunodominant non-OmpA proteins to a lesser extent, resulting in poor assay sensitivity. The specificity of C. trachomatis serology is also compromised by the high prevalence of cross-reactive anti-C. pneumoniae antibodies in human populations. We previously identified 48 highly specific C. trachomatis B cell epitope peptide antigens of 21 immunodominant proteins. This study validated peptide antigen-based novel ELISAs that provide highly specific and sensitive detection of anti-C. trachomatis antibodies. Compared to four commercial ELISAs that achieved only poor sensitivities (51.5% to 64.8%), the combined signals of 5 to 11 peptides provided high sensitivity (86.5% to 91.8%) at the same 98% specificity. Thus, by using multiple peptide antigens of immunodominant proteins, we created simple ELISAs with specificity and sensitivity superior to standard C. trachomatis serodiagnosis.